Distance Learning and Multimedia Teaching Education: E-Laboratory Activities during Covid-19 Pandemic. Issue 1 (1st June 2022) - Fiore, Oriana; Adesso, Maria Giuseppina; Capone, Roberto
Abstract: During the COVID-19 pandemic lockdown, Italian schools and Universities were closed. In this scenario, teachers, in order to continue their work, had to manage the didactics by themselves, carrying out Distance Learning, thanks to the technology support. Nevertheless, teachers had some methodological and technical difficulties. This situation required the replanning of some physics contents, trying to include laboratory activities, too. A teachers' training was organized in order to support the teachers both for effective and meaningful use of ICT and to carry out some laboratory activities in Distance Learning mode. The training aimed to investigate leading technologies relevant to physics teaching, the competencies that a physics teacher has to acquire to use digital technologies, and the effective approaches to develop these competencies. The course was organized into four webinars, timing 10 hours. Teachers became confident with ICT for communication, sharing, and documentation. Moreover, teachers approached the IBSE methodology, as modified by adding a further E-laboratory phase to the 5E cycle, promoted by Bybee, by planning a learning chunk, including a laboratory activity in synchronous e-learning mode. 20 High School Physics teachers were involved in the training.